Big Data analysis for drilling and blasting in a mine in the Central Andes - Mallqui Carhuamaca, Jhordan Jean Pier (2021)
Big Data applied to mining, contemplates the combi- nation of algorithms located in advanced technological tools to process a quantity of data, Power BI allows the interaction of dif- ferent data formats, for integration it has the support of Python Script. In this article, Big Data was applied to essential activities such as drilling and blasting, analyzing the parameters, standards, quantities, advances, the objective was to develop an integration system of a quantity of data for its analysis and interpretation, it will contribute to decision making in the mining operation. The development of Dashboard for interactive reportability based on indicators, will allow to visualize more efficiently and in a virtual way among the interested parties. Finally, the application of Big Data in the field of mining mainly in the treatment of its data will be the trend of the future which will allow to optimize the time and the functionality of the reports.